2007
DOI: 10.2500/aap.2007.27.2904
|View full text |Cite
|
Sign up to set email alerts
|

Association between previous enterobiasis and current wheezing: Evaluation of 1018 children

Abstract: The aim of this study was to investigate the association between parasitosis and allergy. We surveyed all children aged 4-12 years living in poor hygienic conditions in a shantytown of Istanbul. After obtaining data from the International Study of Asthma and Allergies in Childhood (ISAAC) and an additional questionnaire, performing a skin-prick test (SPT), and determining total IgE, stool and perianal tape specimens were obtained from 1018 participating children. The prevalence of past episodes of wheezing, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
2
16
2
Order By: Relevance
“…The majority of studies were published within the past 10 years. As 19 of the 21 included studies were carried out in Central or South America or Africa, [the remaining two studies were from Vietnam (23) and Turkey (18)], our findings are particularly applicable to those regions of the world; though, there are no grounds to suggest that the findings will not be generalizable elsewhere where similar environmental conditions exist. While our primary analysis was for infection with any parasite, the majority of parasites were, in fact, geohelminths, and it may be that other parasite infections will demonstrate a different relationship with atopy but further studies are needed before any conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The majority of studies were published within the past 10 years. As 19 of the 21 included studies were carried out in Central or South America or Africa, [the remaining two studies were from Vietnam (23) and Turkey (18)], our findings are particularly applicable to those regions of the world; though, there are no grounds to suggest that the findings will not be generalizable elsewhere where similar environmental conditions exist. While our primary analysis was for infection with any parasite, the majority of parasites were, in fact, geohelminths, and it may be that other parasite infections will demonstrate a different relationship with atopy but further studies are needed before any conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 88%
“…Pooled results from the three studies of Schistosomiasis species (16, 17, 29) found current infection was associated with a statistically significant reduction in the odds of current atopy (OR 0.12, 95% CI 0.03–0.57; P = 0.007); however, the results from these studies were heterogeneous ( I 2 = 69%) and all three studies were scored as having lower methodological quality (Figs 6 and Table S1). No effect on the risk of current atopy was seen with E. vermicularis (18, 30), Giardia intestinalis (18), or Blastocystis hominis (18).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations